2015
DOI: 10.1016/j.jcf.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of pulmonary exacerbation in cystic fibrosis: A Delphi survey of patients and health professionals

Abstract: There were clear differences in perspectives between the two groups as to the most important indicators of an exacerbation. This highlights that CF health professionals should take more cognisance of specific signs and symptoms reported by adults with CF, especially since these may be a precursor to an exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…At the time of AE, the mean variation of FEV1 relative to the best personal value was −0.26 ± 0.22 L, similar to several studies that reported decrease in FEV1 in a context of AE (McCourt et al., 2015; Sanders et al., 2011). Improvement of FEV1 value after AE treatment is also reported (Hoppe et al., 2018; Ren et al., 2006; Wagener et al., 2020).…”
Section: Discussionsupporting
confidence: 87%
“…At the time of AE, the mean variation of FEV1 relative to the best personal value was −0.26 ± 0.22 L, similar to several studies that reported decrease in FEV1 in a context of AE (McCourt et al., 2015; Sanders et al., 2011). Improvement of FEV1 value after AE treatment is also reported (Hoppe et al., 2018; Ren et al., 2006; Wagener et al., 2020).…”
Section: Discussionsupporting
confidence: 87%
“…The lung disease of CF is characterized by chronic persistent infection and inflammation that is punctuated by intermittent episodes of worsening signs and symptoms that are labeled as pulmonary exacerbations and typically treated with systemic antibiotics [9]. While it has long been appreciated that pulmonary exacerbations are a significant driver of the longterm loss of lung function in patients with CF [20,21], there is lack of consensus regarding their definition and treatment [9,18,22,23], leading to inconsistencies in both [6,10,18,24]. Registry analyses have documented the surprising proportion of exacerbations that are left untreated [6,25,26], especially in patients with relatively preserved baseline lung function [10], as well as the unsurprising fact that treatment mitigates a subsequent deterioration in ppFEV1 and the development of worsening signs and symptoms of lung disease [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…signs and symptoms) or administration of antibiotics as clinical endpoints 21 . For this study, an unvalidated modification of the Fuchs exacerbation endpoint was used.…”
Section: Discussionmentioning
confidence: 99%